Efecto del extracto acuoso de la Ocimum basilicnum l. (albahaca) en el crecimiento bacteriano de Escherichia coli - Calderon Mestanza, Jherson (2018)
This study is of research design experiment, completely randomized with 4 treatments and 1 control group, with 3 repetitions. Whose overall objective was to determine the antibacterial effect of aqueous extract of basil (Ocimum basilicum l.) in bacterial growth of Escherichia coli, in order to provide scientific support to popular knowledge. Worked on a sample of 15 petri dishes with strains of Escherichia coli and plant material basil (Ocimum basilicum l.) Fresh. The results show a positive effect of antibacterial activity at doses of 5g, 10g, and 20g water extract of basil (Ocimum basilicum l.) On the growth of Escherichia coli bacteria whose antibacterial effect dose aqueous extract 5g basil (Ocimum basilicum l.) was 38% for 10g was 43.5%, and 46.5% was 20g. In conclusion bacterial growth of Escherichia coli significantly reduces the effect of three doses (5g, 10g and 20g) of aqueous extract of basil (Ocimum basilicum l.) community from Turning Lady of the Amazon Region, being the 20mg which had higher antibacterial activity.